Конструктивно-технологічна схема гичкозбирального агрегату з використанням орно-просапного трактора - Ігнатьєв, Євген Ігорович; Игнатьев, Евгений Игоревич; Ihnatiev, Yevhen (ТДАТУ, 2017)
The expediency of collecting and using such valuable raw materials as sugar beet tops is proved in the work. In this connection, a well-grounded constructive and technological scheme of combined unit for harvesting beet tops was proposed, and the main operational parameters tops were also given.
Keywords: sugar beet; tops; harvesting; cutting without sensing; defoliating; constructive scheme; technological scheme